2016
DOI: 10.1039/c6nr07504e
|View full text |Cite
|
Sign up to set email alerts
|

Super-oxidation of silicon nanoclusters: magnetism and reactive oxygen species at the surface

Abstract: Oxidation of silicon nanoclusters depending on the temperature and oxygen pressure is explored from first principles using the evolutionary algorithm, and structural and thermodynamic analysis. From our calculations of 90 SiO clusters we found that under normal conditions oxidation does not stop at the stoichiometric SiO composition, as it does in bulk silicon, but goes further placing extra oxygen atoms on the cluster surface. These extra atoms are responsible for light emission, relevant to reactive oxygen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…34,35 The energies of 10 best structures for each composition were refined using the GAUSSIAN code 36 with the B3LYP/6-311+G(2d,p) approach. 37 Comparison of our results with earlier publications 4,6,10,[26][27][28][30][31][32][33] showed that 101 optimal structures of Si n O m clusters were correctly reproduced by us, 17 better ones were found, and 197 clusters were studied for the first time to our best knowledge (see table 1 in SI). Fig.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…34,35 The energies of 10 best structures for each composition were refined using the GAUSSIAN code 36 with the B3LYP/6-311+G(2d,p) approach. 37 Comparison of our results with earlier publications 4,6,10,[26][27][28][30][31][32][33] showed that 101 optimal structures of Si n O m clusters were correctly reproduced by us, 17 better ones were found, and 197 clusters were studied for the first time to our best knowledge (see table 1 in SI). Fig.…”
supporting
confidence: 74%
“…315 cluster compositions). We note that the earlier investigations of Si n O m were either done for relatively small clusters (n ≤ 7) 6,26,28,30,31 or focused on stoichiometric compounds (SiO) n or (SiO 2 ) n . 4,10,27,32,33 Even for these compounds it is often seen that newer papers report lowerenergy structures than the older ones.…”
mentioning
confidence: 99%
“…Furthermore, the chemistry of nanoparticles can be very sensitive to the chemical environment and quite unexpected cluster compositions can be 'magic' (that is, particularly stable; for example this was shown for Fe-O and Ce-O clusters [85]). It has been shown that under normal conditions (300 K and 0.21 atmospheres partial pressure of O2) the predominant Si7Om, Fe4Om, and Ce4Om nanoparticles are oxygen-rich magnetic Si7O19, Fe4O8, Ce4O14 clusters rather than 'normal' Si7O14, Fe4O6 and Ce4O8 [85,86]. The presence of reactive oxygen species (such as ozo-nide-groups O3 2-) in such clusters may explain the known carcinogenicity of small silica particles [87].…”
Section: [H1] Introductionmentioning
confidence: 99%
“…Quartz and cristobalite dust are known as carcinogens, in contrast to stishovite 42 . One hypothesis connects toxicity of silica dust with the presence of reactive oxygen species on the surface, and these were found with electron paramagnetic resonance in cristobalite dust 43 and theoretically predicted on α-quartz (011) surface 44 and in silica nanoclusters 45 . “Dense” surfaces described here have no reactive oxygen species.…”
Section: Discussionmentioning
confidence: 96%